If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8q+12=4(3q-2)
We move all terms to the left:
8q+12-(4(3q-2))=0
We calculate terms in parentheses: -(4(3q-2)), so:We get rid of parentheses
4(3q-2)
We multiply parentheses
12q-8
Back to the equation:
-(12q-8)
8q-12q+8+12=0
We add all the numbers together, and all the variables
-4q+20=0
We move all terms containing q to the left, all other terms to the right
-4q=-20
q=-20/-4
q=+5
| 9b-8b=9 | | 5-4j=45 | | 2n+3=42+4n | | 19d-10d=9 | | 8x+4=4(2x+1 | | 13/169=4/x | | 34=-2(r-97) | | 2n+3=42+4 | | 12k^2-455=-7+5k^2 | | -9(6+c)-2c=-10 | | 16r-14r=20 | | 85=13+8f | | x2–4x+6=0 | | 3/4x-4=3 | | 6v+10=100 | | 12y^2-24y-36=0 | | 4z+5z=18 | | 48=—11t+18+2t | | 24-2n=8 | | 17.53+16a-20=32.5a | | 3/2x+14=3x+4 | | 3(h-77)=36 | | (4x-35)=3x+10 | | 10x+6x=4-4x | | 25=2g-11 | | 48=8+5x | | 9x-5(x-17)=-35-2(5x-3) | | 88=4(j+14) | | 3/4w=131/2 | | 3x^2+18x+6=6 | | -1/3+3/5g=-10/3 | | -5w+6=31 |